EVALUASI PERLAKUAN AKUNTANSI ATAS PIUTANG TAK TERTAGIH PADA PT. ANGKASA PURA I (PERSERO) CABANG MANADO - Logor, Ribka Josevira; Sabijono, Harijanto; Alexander, Stanly W. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The Bad Debts is very influential on the decline in operating profit of the companyThis study aims to determine the presentation, recognition and measurement and disclosure of uncollectible receivables at PT. Angkasa Pura I (Persero) Manado Branch and conformity with PSAK 50, 55 and 60. This study uses qualitative research methods with descriptive methods. The evaluation method used is collecting data obtained through interviews and documentation, then analyzing the data and finally data processing data. The results of this study are receivables which are categorized into uncollectible receivables, namely receivables that have more than 6 months of maturity. The treatment of uncollectible receivables from PT. Angkasa Pura I (Persero) complies with Financial Accounting Standards namely PSAK 50, 55, and 60. The accounting treatment of uncollectible receivables must also be given special attention by companies to minimize uncollectible receivables.